Effect of Donor and Recipient ABH-Secretor Status on ABO-Incompatible Living Donor Kidney Transplantation - Zhang, Fan; Yin, Saifu; Fan, Yu; Song, Turun; Huang, Zhongli; Liang, Jiayu; Wu, Jiapei; Yang, Youmin; Lin, Tao; Wang, Xianding (Frontiers in Immunology, 2021)
Introduction ABO blood group antigens within grafts are continuously exposed to anti-A/B antibodies in the serum of recipients after ABO-incompatible (ABOi) kidney transplantation and are instrumental in antibody-mediated rejection. Some individuals secrete soluble blood group antigens into body fluids. In this study, we investigated the effect of donor and recipient secretor status on the outcomes of ABOi kidney transplantation. Methods Data of a total of 32 patients with ABOi living donor kidney transplantation were retrospectively collected between 2014 and 2020 in West China Hospital. The genotype and phenotype of both donors and recipients were examined and evaluated with post-transplantation anti-A/B titer changes, graft function, and rejection. Results Of the 32 recipients and 32 donors, 23 (71.9%) recipients and 27 (84.4%) donors had secretor genotypes, whereas 9 (28.1%) recipients and 5 (15.6%) donors did not. Anti-A/B titers after ABOi kidney transplantation were not significantly influenced by the secretor status of either donors or recipients. The post-transplantation serum creatinine (Scr) levels and estimated glomerular filtration rate (eGFR) was better in weak- or non-secretor recipients at day 30 (Scr P = 0.047, eGFR P = 0.008), day 90 (Scr P = 0.010, eGFR P = 0.005), and month 9 (eGFR P = 0.008), and recipients from secretor donors had a lower incidence of graft rejection in the first year after ABOi transplantation (P = 0.004). Conclusions A weak secretor status phenotype was found in both genotypes, i.e., individuals who secreted soluble antigens as well as those who did not. The recipient ABH-secretor status may have an influence on early posttransplant renal function, and the donor ABH-secretor status might affect the incidence of graft rejection.